Impacto de las nuevas tecnologías en el negocio bancario espa\~nol - J. L. Fanjul Suárez; L. Valdunciel Bustos (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
Among the conventional strategic business models, companies decide which technologies should be used. Contrary to that, at present, technology takes the strategic decisions in businesses playing a role totally unknown so far. The way of managing businesses has modified the fundamental economic assumptions on which the vast majority of businesses were based transforming the industrial economy into what now is called digital economy. The impact of this new economy is uneven depending on the sectors. The financial sector has pioneered the use of Internet as a new distribution channel. Internet development allows a sustainable growth because the distribution of financial products does not require a physical exchange of goods. The reason is that money has been, for a long time, an electronic good. This paper tries to analyze the situation of online banking in Spain, the strategies adopted by the most important financial concerns in the country, and how this new channel has influenced the financial products offered by those concerns.
Keywords: 330; CIT; new economy; online banking